EXTH-35. INCREASING THERAPEUTIC INDUCED NEURAL STEM CELL PERSISTENCE IN THE GLIOBLASTOMA TUMOR RESECTION CAVITY. (12th November 2021) - Bomba, Hunter; Kass, Lauren; Sheets, Kevin; Carey-Ewend, Abigail; Goetz, Morgan; Bago, Juli; Khagi, Simon; Hingtgen, Shawn; Findlay, Ingrid
Abstract: BACKGROUND: Induced neural stem cells (iNSCs) have emerged as a promising therapeutic platform for glioblastoma (GBM). iNSCs have the innate ability to home to tumor foci, making them ideal carriers for anti-tumor payloads. However, iNSC persist for only two weeks in the murine GBM tumor resection cavity. We hypothesized that by encapsulating iNSCs in a scaffold matrix, we could increase both the persistence of the cells the therapeutic durability. METHODS: iNSCs expressing TRAIL were encapsulated in a gelatin-thrombin matrix; fibrinogen was used to polymerize the matrix. SEM was used to explore interactions between iNSCs and the scaffold matrix. To evaluate persistence, iNSCs encapsulated in the matrix were implanted into mock resection cavities of athymic nude mice and followed via BLI. To study the impacts of encapsulation on iNSC efficacy, athymic nude mice were implanted with U87 or GBM8 tumors. Tumors were then resected, and iNSCs encapsulated in the matrix were implanted; tumor volume was monitored via BLI. RESULTS: SEM images showed homogeneous distribution of iNSCs throughout the matrix; iNSCs were completed encased in the fibrin clot component of the matrix and did not adhere to gelatin. In vivo, encapsulated iNSCs persisted for nearly 100 days whereas iNSCs directly injected into the brain parenchyma persisted < 20 days. Using mice bearing GBM8 tumors, animals treated with a high dose of therapeutic encapsulated iNSCs survived ~60 days longer than animals treated with non-therapeutic cells. A similar trend was observed in animals inoculated with U87 tumors. While not statistically significant, 25% of mice treated with iNSCs encapsulated in the gelatin-thrombin matrix survived longer than those treated with iNSCs encapsulated in a fibrin-only matrix, suggesting additional benefit due to the gelatin component. FUTURE DIRECTIONS: Prospective experiments will explore the impact of the scaffold on iNSC phenotype, including proliferation, differentiation, and migration markers.